2017
DOI: 10.4103/ijccm.ijccm_445_16
|View full text |Cite
|
Sign up to set email alerts
|

Critically ill obstetric patients in a general critical care unit: A 5 years′ retrospective study in a public teaching hospital of Eastern India

Abstract: Background:Critical care services are essential for the subset of obstetric patients suffering from severe maternal morbidity. Studies on obstetric critical care are important for benchmarking the issues which need to be addressed while managing critically ill obstetric patients. Although there are several published studies on obstetric critical care from India and abroad, studies from Eastern India are limited. The present study was conducted to fill in this lacuna and to audit the obstetric critical care adm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
24
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 29 publications
7
24
1
Order By: Relevance
“…The ICU admission rate was found to be 0.4 to 1.2% in other Indian studies. [8][9][10][11][12][13] In developed world the ICU admission rate has been reported to be between 0.7-13.5%. 4 The reason for high ICU admission rate is simply because of poor antenatal supervision, non instituitional deliveries, late recognition of complications and delayed referral.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The ICU admission rate was found to be 0.4 to 1.2% in other Indian studies. [8][9][10][11][12][13] In developed world the ICU admission rate has been reported to be between 0.7-13.5%. 4 The reason for high ICU admission rate is simply because of poor antenatal supervision, non instituitional deliveries, late recognition of complications and delayed referral.…”
Section: Discussionmentioning
confidence: 99%
“…8,9 However in some studies obstetric haemorrhage has been reported as the commonest cause of ICU admission. 10,12,13 In one of the studies septicemia has been found to be the commonest indication for ICU admission. 11 In developed countries the indications for admissions have varied between centres primarily because of the different referral nature of these hospitals which might be the reason for the observed heterogeneity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Very few studies have been conducted in India evaluating the reason for ICU admissions of critically ill obstetric patients in tertiary hospitals across India. [10][11][12] The present study was conducted to evaluate the indications for admission, course and outcome of the critically ill obstetric patients in Kashmir valley, in order to evaluate the patient characteristics of critically ill obstetric patients so that high risk obstetric patients are identified early and managed appropriately with early involvement of multidisciplinary obstetric intensive care team.…”
Section: Introduction:-mentioning
confidence: 99%